PEMANFAATAN EKSTRAK TANAMAN PARASITTALI PUTRI (CASSYTHA FILIFORMIS L.) SEBAGAI INSEKTISIDA NABATIPADA HAMA WERENG COKLAT (NILAPARVATA LUGENS) - dan Nur Hidayah, Danar, Dewi Rachmawati, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This study aims to determine the effectiveness of the process of making and using vegetableinsecticide with basic materials Doddel Laurel (Cassytha filiformis L) of the brown planthopper(Nilaparvata lugens).The method used has two stages, namely 1). Preparation Extracts Doddel Laurel (Cassythafiliformis L)) as the solution of the Master, 2). Implementation Testing Laboratory Scale.The results of this study is doddel laurel (Cassytha filiformis L) has the potential to be used as abotanical insecticide. The process of making botanical insecticide with doddel laurel (Cassytha filiformisL) has 2 stages of preparation for the extract doddel laurel (Cassytha filiformis L) as the solution of theMaster consist of washing, cutting, drying, extracting, and screening and testing laboratory scale consistof variationing concentration of solution, adaptation brown planthopper, botanical insecticide spraying,and observations. The use of botanical insecticide with basic material doddel laurel (Cassytha filiformis L)against brown planthopper (Nilaparvata lugens) has not been as effective as compared with decis within900 seconds. The use of 25%, 50%, 75% and 100% botanical insecticide with basic materials doddel laurel(Cassytha filiformis L) was able to take the death brown planthopper in a row are 1 head, 1 tail, 2 tailsand 3 tails. Compared with decis that take the death of 4 brown planthoppers. The recommendedsolution is to extract with 100% concentration having the time of death is the shortest.Keywords: Doddel Laurel, botanical insecticide, brown planthopper